Gut microbiome and metabolome interactions in Crohn’s disease: mechanistic insights into exclusive enteral nutrition-induced remission - Zheng, Weiwei; Zhou, Quan; Xue, Mengli; Yu, Xing; Chen, Xue’e; Chen, Jintong; Wang, Chengdang (Frontiers in Microbiology, 2025)
BackgroundExclusive enteral nutrition (EEN) is a first-line therapeutic approach for inducing remission in Crohn’s disease. However, the underlying mechanisms of its action remain poorly understood. This study aims to investigate the effects of EEN on the gut microbiome and metabolome of CD patients and to elucidate the mechanisms responsible for EEN-induced remission.MethodsFecal and blood samples were collected from treatment-naïve CD patients (n = 25) both before and after 8 weeks of EEN therapy, as well as from healthy control subjects (n = 25). The composition of the gut microbiome was analyzed through 16S rRNA gene sequencing, while metabolomic profiling was conducted using liquid chromatography–mass spectrometry (LC–MS). Functional analysis of microbial pathways was performed utilizing the KEGG Orthology (KO) and MetaCyc databases.ResultsEEN therapy induced significant structural shifts in the gut microbiome, including a reduction in the abundance of pro-inflammatory bacteria such as Fusobacterium and Veillonella. Metabolomic profiling revealed stage-specific metabolic reprogramming, with notable alterations in phenazine biosynthesis, indole diterpene alkaloid biosynthesis, and sphingolipid metabolism. Functional analyses indicated the activation of energy metabolism pathways and the suppression of pro-inflammatory metabolic pathways. Importantly, EEN therapy was associated with a reduction in oxidative stress and an improvement in gut barrier function.ConclusionThis study comprehensively integrates microbiome and metabolome analyses, providing new insights into the mechanism of action of EEN therapy in CD. EEN exerts therapeutic effects by restoring metabolic balance and enhancing the integrity of the intestinal barrier, which may be achieved by reducing pro-inflammatory bacteria and activating antioxidant and energy metabolism pathways.